Synthesis and Characterization of Carbon-11 Labeled Iloperidone for Imaging of α1-Adrenoceptor in Brain - Xu, Yulong; Wang, Yanli; Wang, Hao; Wang, Changning (Frontiers in Molecular Biosciences, 2020)
α1-Adrenoceptor is implicated in numerous neuronal diseases. The development of new modulators targeting this receptor as well as the investigation of the role of α1-adrenoceptor in healthy and disease conditions, however, is hindered by the lack of specific positron emission tomography (PET) radiotracers. Iloperidone shows a high binding affinity to α1-adrenoceptor and moderate selectivity over other brain receptors. We report herein the synthesis and characterization of carbon-11 labeled iloperidone for imaging of α1-adrenoceptor in brain. The radiolabeling of [11C]iloperidone was carried out conveniently in one step by treating precursor with [11C]CH3I in DMF in the presence of K2CO3. Then, [11C]iloperidone was purified by semi-preparative HPLC, and characterized in C57BL/6 mice using PET/CT scanning. The desired product [11C]iloperidone was obtained in an average decay corrected radiochemical of 12% (n = 3) and over 99% radiochemical purity. The average molar radioactivity was 357 GBq/μmol with total synthetic time of 35-40 min. PET/CT scanning in C57BL/6 mice showed favorable pharmacokinetic properties and high brain exposure of [11C]iloperidone. Blocking experiments by pretreatment with the unlabeled iloperidone showed the significant blocking effects with about 25% reduction in brain uptake. These results suggested that [11C]iloperidone can serve as a lead compound for the further development of specific radiotracers for PET imaging α1-adrenoceptor in brain clinically.